Adaptive Filtered-X LMS algorithm for active vibration control on micron positioning stage - Yun-Hui Liu; Hong-Jen Lee (2012 International Conference on Control, Automation and Information Sciences, 2012)
The objective of this study is to develop an active vibration control (AVC) system to suppress the relative displacement between lens set and granite platform using a micron positioning stage, installed between lens set and gantry. This control system applies Filtered-X LMS adaptive algorithm as the controller, and uses the vibration signal measured by accelerometer as input signal to generate a control signal that drives piezoelectric actuator to produce anti-force to suppress vibration of the micron positioning stage. The goal of this study is to reduce 50% amplitude of the horizontally relative displacement between the lens set and granite platform under a frequency range of 1 ~ 10Hz. Through the experiments of active control, it was verified that the vibration of stage is effectively decreased to 2 ~ 4μm from 12 ~ 20μm after control under the proposed frequency range.